The sorceress - Scott, Michael, 1959- (Scott, Michael, 1959- Secrets of the immortal Nicholas Flamel, 2009)
While armies of the Shadowrealms gather and Machiavelli goes to Alcatraz to kill Perenelle Flamel, fifteen-year-old twins Sophie and Josh Newman accompany the Alchemist to England to seek Gilgamesh.